Assessment of the antioxidant activity of the extrcat, cold press, and n-hexane oils and in vitro cytotoxic effects of Capparis spinosa L. seed on SH-SY5Y cancer cell lines - Leila Ghassemifard; Saeed Sardari; Hajar Safari; Hajar Ramezanikhah; Narjes Khavasi (Institue of Medicinal Plants, ACECR, 2022)
Background: Capparis spinosa L. due to its anti-inflammatory and antioxidant properties plays a key role in preventing and treatment of cancer, also reduces the growth rate of cancer cells. This plant can be used in various ways in medicinal compounds, food, etc. as an extract, oil, or essential oil. Objective: In the current study, the rate of antioxidant activity extracts and oils (cold press and n-hexane oils) of Capparis seeds and also the effect of the seeds on the SH-SY5Y cell line have been investigated. Methods: First, extract, cold press, and n-hexane oils were prepared; then all reached concentrations of 50, 100, and 200 mg/ml, and their antioxidant capacity was evaluated by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. After that, the number of antioxidant compounds in the extract was measured, and finally, the toxicity of the extracts was evaluated by the (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) method on SH-SY5Y cancer cells. Results: The IC50 data showed that the antioxidant activity of the Capparis seeds extracts was significantly (P < 0.001) increased compared to cold press and n-hexane. Antioxidant compounds analysis of Capparis seeds extract indicated high rate of total phenolic, flavonoid as rutin, and quercetin. MTT assay demonstrates that Capparis seeds extracts in a concentration of 1000 μg/ml decreased the viability of the SH-SY5Y cancer cell lines in comparison with hacked cells (P < 0.001). Conclusion: The seed extract of Capparis seeds at high concentrations, probably due to its high antioxidant content, inhibits the growth of SH-SY5Y cancer cells.